Kierkegaard on the Possibility of Justice in this World - Kos, Bert (Kierkegaard studies. Yearbook, 2025)
This article examines how the concept of faith in Kierkegaard’s Fear and Trembling can be understood as a response to an experience of crisis arising from the perceived injustice of the external world. Initially, this crisis isolates the individual and prevents him from truly participating in state and society. I contrast this movement of isolation with the ethical movement of becoming a universal individual as described in both Either/Or and Fear and Trembling. The faithful individual does not remain isolated; through faith, he establishes a new relation to life with others in state and society. Rather than withdrawing from this world and fixating on an ideal world beyond it, the faithful individual trusts that our efforts to strive for justice here and now are meaningful. I discuss some characters from Fear and Trembling —the tax collector, Sarah, and Gloucester—that serve as (counter)‌examples for this more social and practical interpretation of faith.